2013
DOI: 10.1159/000355647
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Morbidity and Mortality among Veterans Health Administration Patients Undergoing Surgical Resection for Large Bowel Polyps (Bowel Resection for Polyps)

Abstract: Background: Large bowel polyps with malignant characteristics or those that are too large to remove colonoscopically may require bowel resection. Method: We performed a retrospective review of 126 Veterans Health Administration patients who underwent elective resections for colonoscopically unresectable colorectal polyps over a 10-year period. We evaluated the association of patient characteristics and operative management on the composite outcome of 30-day postoperative morbidity and mortality. Results: 98% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Mortality in our cohort was generally similar to one study, 15 markedly lower compared with another series, 14 and substantially lower than estimated by scoring systems designed to predict operative mortality. 13 The risk of major morbidity (15%) in our cohort was similar to most prior estimates 9, 15 and lower than 2 small series.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Mortality in our cohort was generally similar to one study, 15 markedly lower compared with another series, 14 and substantially lower than estimated by scoring systems designed to predict operative mortality. 13 The risk of major morbidity (15%) in our cohort was similar to most prior estimates 9, 15 and lower than 2 small series.…”
Section: Discussionsupporting
confidence: 82%
“…Surgical resection can be complicated by the need for an ostomy, postoperative infection, wound dehiscence, readmission, reoperation and death. Prior estimates of these risks have included hypothetical models, 13 small numbers of cases, 7, 14, 15 or limited detail on morbidity with no mortality estimates. 9 Understanding the risks associated with surgical resection is necessary to make an informed decision whether to pursue surgery versus endoscopic resection.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our mortality and morbidity estimates are more generalizable, particularly in non-NSQIP participating US institutions. In cohort-based studies, similarly high risks of postoperative adverse events have also been reported at 20%–30%, although these estimates are limited by sample size considerations (14,23).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a strong correlation between lesion size and its potential for malignancy (2,4,32) , and these lesions are considered to be at higher risk for submucosal invasion and lymph node involvement (9) . A greater malignant potential for lesions >10 mm (P<0.0001) was observed by Reinhart et al (23) , regardless of morphology.…”
Section: Discussionmentioning
confidence: 99%